EXPLORING GENERATION Z’S PRE-VISIT PERCEPTIONS OF RURAL TOURISM: A DESCRIPTIVE STUDY OF NON-VISITORS - Julian Bongsoikrama; Nexen Alexandre Pinontoan (Journal of Innovation Research and Knowledge, 2026)
This study aims to explore Generation Z’s pre-visit perceptions of rural tourism among individuals who have never visited rural tourism destinations. Using a quantitative descriptive design, data were collected from 457 Generation Z respondents through an online questionnaire. The study measured three perceptual dimensions: cognitive perception, affective perception, and perceived authenticity. Data were analyzed using descriptive statistics, including mean scores and standard deviations. The findings reveal that overall pre-visit perceptions of rural tourism are positive. Among the three dimensions, perceived authenticity obtained the highest mean score, indicating that rural tourism is primarily associated with genuine local culture, preserved traditions, and natural experiences. Affective perception also showed strong results, suggesting that rural tourism is emotionally framed as relaxing, enjoyable, and meaningful. Meanwhile, cognitive perception, although categorized as high, recorded relatively lower scores in indicators related to facilities and accessibility. These results suggest that rural tourism is positioned more strongly in symbolic and emotional terms rather than functional aspects in the minds of Generation Z non-visitors. The study highlights the importance of strengthening communication strategies that emphasize authenticity while also improving and clearly conveying information about infrastructure and accessibility. Understanding these pre-visit perceptions is essential for designing more effective promotional strategies to attract younger potential tourists.